Studi Karakteristik Pada Kejadian Ibu Hamil KEK Di Puskesmas Kotabaru - Salna Fitriana; Hartinah Hartinah; Ika Friscila (Lembaga Pengembangan Kinerja Dosen, 2024)
Research background: Chronic Energy Shortage (KEK) is still a problem in Indonesia. Women and children are the groups at highest risk of experiencing Chronic Energy Deficiency (CED). Currently Chronic Energy Deficiency (CED) is a concern for the government and health workers, because a woman of childbearing age (WUS) who experiences CED has a high risk of giving birth to a child who will also experience CED in the future. The aim of the research is to identify study characteristics of the incidence of CED pregnant women at the Kotabaru Community Health Center. The research method uses quantitative descriptive. The population is all 30 KEK pregnant women at the Kotabaru Community Health Center in October – December November 2023. The sample was taken using a total sampling technique of 30 people. Data were analyzed univariately. The results of the research were that age characteristics were the most common in the risk category with a percentage of 66.7%. Parity characteristics were most common in the multiparous group at 50%. The characteristics of pregnancy spacing in the risk category were 56.7% and the highest level of education among respondents was at the middle level, namely 40%.